Readiness Of Health Workers To Implement Digital Integrated Patient Progress Notes For Interprofessional Collaboration: A Conceptual And Systematic Review - Mera Delima; Tanti Anggreiniboti; Regidor III Dioso (Jurnal Ners, 2026)
Digital transformation in healthcare services has encouraged the adoption of electronic documentation, including digitally based Integrated Patient Progress Notes (IPPN). The implementation of this system has the potential to enhance the effectiveness of interprofessional collaboration through accurate and real-time access to clinical information. However, the success of implementation is highly dependent on the readiness of health workers. This article aims to examine the readiness of health workers in implementing digitally based Integrated Patient Progress Notes to support interprofessional collaboration and to identify supporting and inhibiting factors. This study employs a conceptual approach and a systematic literature review of scientific articles published from 2018 to 2025 sourced from national and international databases, with the selection process conducted in accordance with the PRISMA 2020 guidelines. The review indicates that digital literacy, technological competence, understanding of clinical documentation, attitude toward innovation, organizational support, training, and infrastructure availability are the main factors influencing readiness for implementation. The application of digital systems has been proven to strengthen interprofessional communication and improve the quality of data-driven clinical decision-making. The implementation of digitally based Integrated Patient Progress Notes has the potential to support interprofessional collaboration if supported by adequate health worker readiness and infrastructure. These findings provide a conceptual framework that can serve as the basis for developing implementation strategies in healthcare facilities. Practical implications include the need for continuous digital literacy training and managerial support in the transformation of technology-based clinical documentation.